2004
DOI: 10.1002/humu.9246
|View full text |Cite
|
Sign up to set email alerts
|

Seven novel mutations of theADAR gene in Chinese families and sporadic patients with dyschromatosis symmetrica hereditaria (DSH)

Abstract: Dyschromatosis symmetrica hereditaria (DSH) is an autosomal dominant pigmentary genodermatosis characterized by hyperpigmented and hypopigmented macules of on the extremities and caused by the mutations in the ADAR gene(also called DSRAD) encoding for RNA-specific adenosine deaminase. Here we reported clinical and molecular findings of 6 Chinese multi-generation families and 2 sporadic patients with DSH. We found that the same mutation could lead to different phenotypes even in the same family and we did not e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 9 publications
3
50
0
Order By: Relevance
“…It should be pointed out that malfunctioning of the editing mechanism and consequent deficiencies in editing of protein coding and non-coding RNAs as well as insufficiency in the interaction between the RNAi and editing pathways may give rise to human diseases and pathophysiology much more complicated than those caused by mutation of a single protein coding gene. Total of 32 mutations (wild-type, green; mutation, red) associated with DSH have been identified in Japanese and Chinese populations [35][36][37][38][39][40][41][42][43][44] . Indicated are Zα and Zβ domains (brown overline), three dsRNA binding domains dsRBD1-3 (yellow filled box), and nine stretches of core deaminase subdomains, highly conserved in all three mammalian ADAR gene family members ADAR1-3 (red box).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be pointed out that malfunctioning of the editing mechanism and consequent deficiencies in editing of protein coding and non-coding RNAs as well as insufficiency in the interaction between the RNAi and editing pathways may give rise to human diseases and pathophysiology much more complicated than those caused by mutation of a single protein coding gene. Total of 32 mutations (wild-type, green; mutation, red) associated with DSH have been identified in Japanese and Chinese populations [35][36][37][38][39][40][41][42][43][44] . Indicated are Zα and Zβ domains (brown overline), three dsRNA binding domains dsRBD1-3 (yellow filled box), and nine stretches of core deaminase subdomains, highly conserved in all three mammalian ADAR gene family members ADAR1-3 (red box).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there seems to be no correlation between genotype and phenotype as carriers with the same mutation show distinct clinical manifestations of the disorder indicating the contribution of environmental factors on disease development and progression 36 . Furthermore, in some of the Chinese pedigrees the penetrance of the ADAR1 mutation was not 100%.…”
Section: Dyschromatosis Symmetrica Hereditariamentioning
confidence: 99%
See 1 more Smart Citation
“…The same mutation will lead to different phenotypes even in the same family, which suggested that environmental factors such as sun exposure could influence the phenotypes. Zhang et al, 2004;Hou et al, 2007;Zhang et al, 2008;Li et al, 2010b;Murata et al, 2010 10 c.3463C>T exon15 p. R1155W -3 Li et al, 2005Li et al, 2010b;Song et al, 2010 In summary, we identified 2 different pathogenic mutations in Chinese patients with DSH, namely E700fsX702 and R474X, the former being a novel mutation. By reviewing all the previously published studies regarding ADAR1 mutations reported since 2003 by using PubMed, we considered that the R474X, R1083C, R1096X, and R1155W mutations might be mutation hotspots.…”
Section: Discussionmentioning
confidence: 65%
“…Autosomal dominant and recessive inheritance patterns as well as sporadic cases of DSH have been described (Oyama et al, 1999). Zhang et al (2004) mapped the gene for DSH to chromosome 1q11-q12, and Miyamura et al (2003) identified mutations in the adenosine deaminase acting on RNA1 (ADAR1) gene that were responsible for DSH among Japanese families. The ADAR1 protein catalyzes the deamination of adenosine to inosine in double-stranded RNA substrates, which results in the creation of alternative splicing sites or codon alternations that lead to functional changes in the protein (Bass and Weintraub, 1988).…”
Section: Introductionmentioning
confidence: 99%